Katolisisme Virtual: Wajah Peribadatan Gereja Katolik Pasca Pandemi Sebuah Diskursus antara Teknologi Komunikasi dan Eklesiologi - Nugraha, Antonius Bagas Prasetya Adi (Perspektif, 2023)
The pandemic has had a severe impact on the whole world, and the Catholic Church is no exception. Catholics, who used to worship in church buildings and face-to-face, had to confine themselves to their homes during the pan[1]demic. The church tries to continue to conduct worship online using the YouTube platform. People with internet networks try to live stream mass from their respective locations. This short article aims to discuss the role of digital media as a means of proclamation for the Church during the pandemic and the polemics that arise later, namely digital media to build virtual Catholicism. The focus of the article is to discuss the difficulties of the Catholic Church in worship during the pandemic associated with the Religious Social-Shaping of Technology (RRST) method to form new creativity to create online wor[1]ship. Even though there are still debates within the Church about whether online worship is valid or not, we should not forget the role of the Holy Spirit. Even in online worship, the Holy Spirit still unites people as a community of faith that believes in God. In fact, it is hoped that the Church can develop and reconcile technology with its distinctive characteristics of Catholicism.